( 7 x − 2 ) 1 / 3 + ( 7 x + 5 ) 1 / 3 = 3
What is the value of x ?
Give your answer to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wow, nice and simple
Log in to reply
For a good problem, it usually has a simple solution. Nice to know that you like the solution.
Log in to reply
Your solutions are always easy and simple even to a tough problem.... @Chew-Seong Cheong
The only method that I can think of to solve this is Newton Raphson Method. Anyone got a better solution?
Anyway, let f ( x ) = ( 7 x − 2 ) 1 / 3 + ( 7 x + 5 ) 1 / 3 − 3
We know that the graph of cube root functions are continuous, and given that:
f ( 1 ) = 5 1 / 3 + 1 2 1 / 3 − 3 ≈ 0 . 9 9 9 f ( 0 ) = ( − 2 ) 1 / 3 + 5 1 / 3 − 3 ≈ − 2 . 5 5 0
From here, we can use the intermediate value theorem to deduce that a root exists in the interval ( 0 , 1 )
Now, use the formula below to find the root:
x n + 1 = x n − f ′ ( x n ) f ( x n )
Let x 0 = 1
f ′ ( x ) = 3 7 ( ( 7 x − 2 ) − 2 / 3 + ( 7 x + 5 ) − 2 / 3 )
x 1 = 1 − f ′ ( 1 ) f ( 1 ) ≈ 0 . 1 9 6 0 7 (I'm lazy to type out the whole thing, you do it yourself)
x 2 = x 1 − f ′ ( x 1 ) f ( x 1 ) ≈ 0 . 7 1 4 4 4
The remaining iterations are:
x 3 ≈ 0 . 3 4 6 9 0 x 4 ≈ 0 . 4 0 9 4 2 x 5 ≈ 0 . 4 2 7 8 1 x 6 ≈ 0 . 4 2 8 5 7 x 7 ≈ 0 . 4 2 8 5 7
Therefore, the value of x that satisfies this equation is x = 0 . 4 2 8 5 7
Notes: The question never stated how many iterations or how many decimal places should our answer be. If it's 3 decimal places, wouldn't it be 0 . 4 2 9 instead of 0 . 4 2 8 ?
And if there is no other method to solve this, does this question belong to Calculus instead?
Problem Loading...
Note Loading...
Set Loading...
( 7 x − 2 ) 3 1 + ( 7 x + 5 ) 3 1 ⟹ y 3 1 + ( y + 7 ) 3 1 ( y + 7 ) 3 1 y + 7 2 y − 9 y 3 2 + 2 7 y 3 1 − 2 0 ( y 3 1 − 1 ) ( 2 y 3 2 − 7 y 3 1 + 2 0 ) ⟹ y 3 1 y 7 x − 2 ⟹ x = 3 Let y = 7 x − 2 = 3 = 3 − y 3 1 Cubing both sides = 2 7 − 2 7 y 3 1 + 9 y 3 2 − y = 0 By rational root theorem = 0 = 1 The only real root = 1 = 1 = 7 3 ≈ 0 . 4 2 8